Practice with idioms - Ronald E Feare (Oxford Univ. Press, 1980)
The book includes Guessing the Meaning from Context, Definition Correspondence, Explanation of the Idioms, and Learning the grammar Rules, as well as multiple choice exercises, writing activities, and suggestions for class discussion. The book also offers review chapters, an appendix of grammatical terms